?SYNTHESIS OF SOME HETROCYCLES FROM DEHYDRO-L-ASCORBIC ACID AND THEIR BIOLOGICAL ACTIVITY (Biological Sciences - PJSIR, 1994)
Sythesis of some hetrocyc1ic compouds from dehydro-L-ascorbic acid, monoaryl hydrazone and their biological activities are described.